Meaning learning model: Implementation, activities and responses of science students - Gonibala, Alfikry; Latjompoh, Masra; Ahmad, Jusna (Journal of Research in Instructional, 2024)
This research aims to measure the implementation of meaning learning, activities and students' responses while they are involved in learning. This research is a quantitative type with a total of 24 students as subjects. The subject is a student at a junior high school in Pinolosian District, South Bolaang Mongondow Regency. Data collection used an observation sheet on learning implementation with 23 aspects, observation of student activities with 6 aspects, and a student response questionnaire with 20 questions. Data was analyzed using the percentage of each acquisition score. The research results show that the implementation of learning is good (3.50 – 4.00), good student activities which are dominated by carrying out literacy activities (reading books) to collect answers. Student responses are positive (91.87) and negative (8.13). The research concludes that learning makes sense carried out well, students become active and they respond well to the learning that has been carried out. Meaning learning needs to be implemented in the classroom in order to create an active and enjoyable learning atmosphere.